The Future of Bioethics in the Context of Globalization (Zien Journal of Social Sciences and Humanities, 2025)
Bioethics, as a discipline that addresses the ethical implications of biological and medical advancements, is increasingly influenced by globalization. This paper explores the future of bioethics in a globalized world, examining the philosophical challenges it faces and the opportunities for developing a more inclusive and equitable framework for ethical decision-making. This paper serves as a foundation for further exploration into the evolving field of bioethics amid globalization, encouraging interdisciplinary collaboration and dialogue for a more equitable future